Verbal Communication Culture and Local Wisdom: The Value Civilization of Indonesia Nation - Kartika, Tina (Lingua Cultura, 2016)
Indonesia is a nation with cultural diversity and area. This caused a lot of the uniqueness of culture in everyday life. This uniqueness was generally a positive value to maintain the harmony of human beings and nature. The discussion of this article was the verbal communication, the study of the wisdom of the nation speech-language Indonesia, and local wisdom in civilization. The words expressed in the local wisdom among others are fearless (need fear only God Almighty), self-sacrificing or spirit of nationalism (patriotism), orderly, loyal, affectionate, hardworking, consensus, mutual help, and creative. Positive values here needed to be crystallized in peopleâ€™s lives; it would be the identifier of the Indonesian people. This research was conducted in five districts of Pagaralam, South Sumatra. The method used was qualitative. Data collection techniques included participant observer/observation, observation without participation, in-depth interviews, and documentation. This article finds that if local wisdom actually exists in everyday life, the nation of Indonesia has carved beauty behave in civilization itself. The local wisdom of the nation begins values, the rule in the family, and then developed in the community. A positive value of local wisdom is the identifier of civilized society and the need to preserve Indonesia.Â